Hydrogen dynamics in heavy alkali metal hydrides obtained through inelastic neutron scattering - Auffermann, G. (2004)
Inelastic neutron scattering spectra from polycrystalline NaH, KH, RbH and CsH, measured at low temperature in the energy transfer range 3 meV < E < 500 meV, are reported. From the medium-energy regions, coinciding with the optical phonon bands, accurate hydrogen-projected densities of phonon states are extracted and compared to ab initio lattice dynamics results. The overall agreement is very good. Further lattice dynamics calculations, based on a pairwise Born–Mayer semi-empirical potential scheme, were also performed, providing only limited and qualitative agreement with the experimental data. In conclusion, incoherent inelastic neutron spectroscopy proves to be a stringent validation tool for lattice dynamics simulations of H-containing materials.